Keterampilan Negosiasi dalam Perkembangan UMKM di Era Globalisasi - Fajaruddin Pakapahan (CV. ULIL ALBAB CORP, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, particularly in employment creation and economic growth. However, in the era of globalization, MSMEs face increasing challenges due to intense market competition and dynamic business environments. One of the key factors influencing the sustainability and growth of MSMEs is negotiation skills, which are closely related to persuasive communication abilities. This study aims to examine the role of negotiation skills in supporting MSME development in the globalization era, with a focus on identifying barriers to persuasive communication and strategies for strengthening them. This research employs a qualitative approach using a literature review method by analyzing relevant scientific journals published between 2020 and 2025. The findings indicate that effective negotiation skills supported by persuasive communication significantly contribute to improving competitiveness, expanding market access, and ensuring business sustainability for MSMEs. Furthermore, strengthening human resource capacity, adapting to cross-cultural communication, utilizing digital technology, and applying ethical and trust-based communication are essential strategies to enhance negotiation effectiveness. This study is expected to provide conceptual insights for MSME development and serve as a reference for academics and practitioners in designing negotiation skill enhancement programs.